2011
DOI: 10.1074/jbc.m111.240739
|View full text |Cite
|
Sign up to set email alerts
|

Detoxication of Structurally Diverse Polycyclic Aromatic Hydrocarbon (PAH) o-Quinones by Human Recombinant Catechol-O-methyltransferase (COMT) via O-Methylation of PAH Catechols

Abstract: Polycyclic aromatic hydrocarbons (PAH)2 are ubiquitous environmental pollutants that are products of fossil fuel combustion and found in tobacco smoke and are suspect lung carcinogens (1, 2). PAH are considered to be procarcinogens and require metabolic activation to elicit their deleterious effects. Benzo[a]pyrene (B[a]P) is a representative PAH and widely used to study the metabolic activation of PAH (3, 4).There are three major pathways for the activation of B[a]P. In the first pathway, P450 peroxidases cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…These studies will document which enzymes attenuate the ability of AKR products to form ROS that can lead to the mutagenic lesion 8-oxo-dGuo. Previously we have shown that PAH o-quinones are enzymatically redox-cycled at a robust rate by recombinant NQO1 and by AKRs themselves and that human COMT can O-methylate a series of PAH-catechols (21,26). In this study we identify SULT1A1 as the major isoform responsible for the formation of B[a]P-7,8-catechol-O-monosulfate based on catalytic efficiency and enzyme expression level in human lung cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These studies will document which enzymes attenuate the ability of AKR products to form ROS that can lead to the mutagenic lesion 8-oxo-dGuo. Previously we have shown that PAH o-quinones are enzymatically redox-cycled at a robust rate by recombinant NQO1 and by AKRs themselves and that human COMT can O-methylate a series of PAH-catechols (21,26). In this study we identify SULT1A1 as the major isoform responsible for the formation of B[a]P-7,8-catechol-O-monosulfate based on catalytic efficiency and enzyme expression level in human lung cells.…”
Section: Discussionmentioning
confidence: 93%
“…In human lung adenocarcinoma (A549) cells with high constitutive expression of AKRs, the metabolic activation of B[a]P-7,8-trans-dihydrodiol to B[a]P-7,8-dione by AKRs led to the formation ROS and 8-oxo-dGuo adducts in cellular DNA, which were exacerbated by the presence of a catechol-O-methyl transferase (COMT) inhibitor (25). The contribution of COMT to detoxication of PAH o-quinone was confirmed by demonstrating that human recombinant COMT detoxified structurally diverse PAH o-quinones, including B[a]P-7,8-dione, via O-methylation of PAH catechols (26).…”
mentioning
confidence: 83%
“…24 Sulfotransferases (SULTs) and catechol-O-methyltransferase would be responsible for the formation of O-monomethyl-O-monosulfonated-catechols. 25,26 The SULTs that are expressed in human HepG2 cells and likely responsible for O-sulfonation are SULT1A1, 1A2, 1E1, and 2A1. 18 γ-Glutamyltranspeptidase, dipeptidase, and N -acetyl transferase would sequentially catalyze the degradation of a GSH-ortho-quinone conjugate to generate the NAC-ortho-quinone conjugate that was detected.…”
Section: Discussionmentioning
confidence: 99%
“…First, the metabolism of gallein may be higher in the kidney, leading to lower intracellular concentrations available for biologic activity. Gallein has a polycyclic catechol structure, which may be a prime target for chemical modification by enzymes such as catechol-O-methyltransferase (COMT) (Zhang et al, 2011). COMT is known to be highly expressed in the kidney, including the S3 segment of the proximal tubule (Meister et al, 1993), and the activity level of COMT is 5-to 8-fold higher in the kidney compared with the heart or brain (Myohanen et al, 2010).…”
Section: Role Of Gbg In Acute Kidney Injurymentioning
confidence: 99%